-(8+x)=-8+7x

Simple and best practice solution for -(8+x)=-8+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8+x)=-8+7x equation:


Simplifying
-1(8 + x) = -8 + 7x
(8 * -1 + x * -1) = -8 + 7x
(-8 + -1x) = -8 + 7x

Add '8' to each side of the equation.
-8 + 8 + -1x = -8 + 8 + 7x

Combine like terms: -8 + 8 = 0
0 + -1x = -8 + 8 + 7x
-1x = -8 + 8 + 7x

Combine like terms: -8 + 8 = 0
-1x = 0 + 7x
-1x = 7x

Solving
-1x = 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-1x + -7x = 7x + -7x

Combine like terms: -1x + -7x = -8x
-8x = 7x + -7x

Combine like terms: 7x + -7x = 0
-8x = 0

Divide each side by '-8'.
x = 0

Simplifying
x = 0

See similar equations:

| -18=18v | | 14x^2+10x-8=0 | | 2(t-4)-3(4t-5)=10-5(7t+3) | | 32+4m=-3(-5m-2)+2m | | -3(n-5)=15+4n | | 6x-2=3x-10 | | 4(1/4+x)=5 | | 7z-4=7z-z | | 6(1+7n)=40+8n | | 2x^2+9x=35 | | -4x^2(5x^2-21x-y)= | | 3(x-1)=-7(x-1) | | 1-5m=6(1-m) | | 7(3x+2)+22=36 | | -0.04x+1.32=1.08 | | 4(6x+5)=2+6x | | -3(4-y)=27 | | -1(3w-4)+12w=3w+4 | | 3m-5=5m+2 | | -27-3k=-6(k+2) | | X+20=6x+5 | | 6-3(2k-4)=-18 | | -3(4-y)=-2 | | r-3.8=9.4 | | -6a+2a=-36 | | 71-17=4a+1 | | 7a-3(a+1)=6-5a | | 1.8+9=-5.7-6 | | 5(3e+5)-25e= | | t^2+9t=18 | | v+31=-3(1-6v) | | 13*4x+2x=1x*6-12 |

Equations solver categories